Efectos del Teletrabajo como modalidad laboral, para los empleados del sector terciario en la ciudad de Bogotá, durante la pandemia ocasionada por el virus SARS -COV-2 (2021)
The purpose of this research is to determine the effects of telework as a work modality based on previous research and studies, as well as on the experience that employees of the tertiary sector have had in the city of Bogotá DC during the pandemic caused by the SARS-CoV-2 virus. The development of this research involves the process of implementation of telework and some important aspects such as its legality, safety, health and well-being, carried out through a type of qualitative research, which allows obtaining a broader and more efficient information on telework, in relation to the increase in this work modality due to the pandemic caused by the SARSCoV-2 virus. This work is part of the organization management research line as well as a sub-line of knowledge management since companies today are in constant development and growth thanks to the fact that they practice continuous improvement, choosing to work with teams. multidisciplinary that give the organization a competitive advantage, obtaining a comprehensive business management that generates greater profitability and benefits for both its clients and the community